Design and Implementation of the New Ticketing Application System with High-Concurrency Supported - Ke Lin; Xuan Luo; Ling Li; Yu Li (Dianxin kexue)
Ticketing application based on mobile internet service is an advanced branch of electronic commerce rising in recent years.It aims to provide convenient services to the user such as query，seat selection，ticket booking，payment and collection.The system performance bottleneck of such services during the high concurrent process was focused on.A new kind of ticketing application system was proposed，which reduced the accessing impact and the business pressure to the native ticketing system.